Strategy for developing small and medium enterprises based on creative economy in facing industrial era 4.0 (study on SMEs in Kupang regency): (Study on SMEs in Kupang Regency) - Manteiro, Maria C. B.; Sahetapy, Stella; Kabu, Enos; Ringa, Maria B. (Institute of Computer Science (IOCS), 2024)
The problems in the research are lack of creativity and innovation, lack of skilled labor, lack of knowledge in product management and marketing that is still done in a conventional way not through automation and e-commerce systems, limited machines and facilities as well as capital for business development. In facing this problem, an appropriate creative economy development strategy is needed so that it can overcome these problems. With the right strategy in the creative industry, it is hoped that UMKM can compete in the 4.0 era and can increase business and regional income. The objectives of this study are 1) To identify and map the existence of culinary and handicraft business SMEs in Kupang Regency.2).This research uses qualitative descriptive methods and formulates appropriate strategies in the field of culinary and knitting business in Kupang Regency. This study took samples in 4 (four) sub-districts in Kupang district, namely east Kupang, Central Kupang, West Amarasi and south Amarasi Samples are selected based on unique business characteristics and have distinctiveness in cultural aspects (aspect culture). Data collection using in-depth interviews, observation and documentation techniques. The result of this research is the formation of a Technology-Based MSME Development Center and Bundling of Creative Industry products